Induction of miR-155 after Brain Injury Promotes Type 1 Interferon and has a Neuroprotective Effect - Harrison, Emily B.; Emanuel, Katy; Lamberty, Benjamin G.; Morsey, Brenda M.; Li, Min; Kelso, Matthew L.; Yelamanchili, Sowmya V.; Fox, Howard S. (Frontiers in Molecular Neuroscience, 2017)
Traumatic brain injury produces profound and lasting neuroinflammation that has both beneficial and detrimental effects. Recent evidence has implicated microRNAs (miRNAs) in the regulation of inflammation both in the periphery and the CNS. We examined the expression of inflammation associated miRNAs in the context of traumatic brain injury using a mouse controlled cortical impact (CCI) model and found increased levels of miR-21, miR-223, and miR-155 in the hippocampus after CCI. The expression of miR-155 was elevated 9-fold after CCI, an increase confirmed by in situ hybridization. Interestingly, expression of miR-155 was largely found in neuronal nuclei as evidenced by co-localization with DAPI in MAP2 positive neurons. In miR-155 knock out mice expression of type I interferons IFNα and IFNβ, as well as interferon regulatory factor 1 and interferon-induced chemokine CXCL10 was decreased after TBI relative to WT mice. Unexpectedly, miR-155 KO mice had increased levels of microglial marker Iba1 and increased neuronal degeneration as measured by fluorojade C staining, suggesting a neuroprotective role for miR-155 in the context of TBI. This work demonstrates a role for miR-155 in regulation of the IFN response and neurodegeneration in the aftermath of TBI. While the presence of neuronal nuclear miRNAs has been described previously, their importance in disease states is relatively unknown. Here, we show evidence of dynamic regulation and pathological function of a nuclear miRNA in TBI.